Use of Eculizumab in Patients With Allogeneic Stem Cell Transplant-Associated Thrombotic Microangiopathy. Issue 9 (September 2015) - de Fontbrune, Flore Sicre; Galambrun, Claire; Sirvent, Anne; Huynh, Anne; Faguer, Stanislas; Nguyen, Stephanie; Bay, Jacques-Olivier; Neven, Bénédicte; Moussi, Julie; Simon, Laurence; Xhaard, Alienor; Resche-Riggon, Matthieu; et al.
<x xml:space="preserve">Abstract</x> Background Thrombotic microangiopathy (TMA) occurring after allogeneic hematopoietic stem cell transplantation (HSCT) has a devastating prognosis. Response rates to current therapies (mainly plasma exchange) are unsatisfactory. Thrombotic microangiopathy after allogeneic HSCT shares similarities with atypical hemolytic uremic syndrome (aHUS) in the underlying pathomechanisms. Eculizumab has been associated with impressive results in aHUS. Materials and Methods We retrospectively analyzed 12 patients who received Eculizumab in France between 2010 and 2013 for severe post-HSCT TMA. Results All 12 patients had severe TMA with neurological and/or renal involvement. Fifty-eight percent were refractory to first-line plasma exchange. At the time of TMA diagnosis, infections were present in 50% of the patients and acute graft-versus-host disease in 33%. Patients were treated with Eculizumab according to the aHUS therapeutic scheme. With a median follow-up of 14 months, hematological response and overall survival were 50% and 33%, respectively. Active acute graft-versus-host disease at TMA diagnosis was the only factor associated with worse overall survival (P = 0.009). Discussion Response rate and overall survival after Eculizumab in our cohort compare favorably with previously published data in TMA after allogeneic HSCT. Prospective trials are warranted to confirm these results. Early initiation of Eculizumab may have a favorable effect on long-term renal function and further contribute to the prolongation of survival.